Aerobic oxidative CC bond cleavage of aromatic alkenes by a high valency iron-containing perovskite catalyst. Issue 7 (4th March 2021) - Shibata, Satomi; Kamata, Keigo; Hara, Michikazu
Abstract : High-valency iron-containing perovskite catalyst BaFeO3− δ could efficiently promote the additive-free oxidative CC bond cleavage of various aromatic alkenes using O2 as the sole oxidant. Abstract : High valency iron-containing perovskite catalyst BaFeO3− δ could efficiently promote the additive-free oxidative CC bond cleavage of various aromatic alkenes to the corresponding aldehydes or ketones using O2 as the sole oxidant. This system was applicable to the gram-scale oxidation of 1, 1-diphenylethylene, in which 2.71 g (75% yield) of the analytically pure ketone could be isolated.